A Multicenter Retrospective Analysis Evaluating Performance of Synovial Biopsy Techniques in Patients With Inflammatory Arthritis: Arthroscopic Versus Ultrasound‐Guided Versus Blind Needle Biopsy. Issue 5 (2nd April 2018) - Humby, Frances; Romão, Vasco C.; Manzo, Antonio; Filer, Andrew; Bugatti, Serena; Vieira‐Sousa, Elsa; Kelly, Stephen; Wechalekar, Mihir; Ahmed, Manzoor; Rocher, Vidalba; Hands, Rebecca; Montecucco, Carlomaurizio; et al.
Abstract : Objective: To evaluate whether the choice of synovial biopsy technique (arthroscopy, blind needle [BN] biopsy, ultrasound [US]–guided portal and forceps [P&F], or US‐guided needle biopsy [NB]) translates to significant variation in synovial tissue quality and quantity, with the aim of informing recommendations for the choice of synovial sampling technique within clinical trials. Methods: In total, 159 procedures from 5 academic rheumatology centers were evaluated. Hematoxylin and eosin–stained, paraffin‐embedded synovial tissue sections from patients with inflammatory arthritis were assessed in order to determine the proportion of graded synovial fragments, total area of graded synovial tissue, and synovitis score per procedure. RNA quantity (μg of RNA) and quality (RNA integrity number) per procedure were also assessed in the synovial samples. Results: In this study, 84 of the 159 procedures performed on large joints at baseline (25 arthroscopic, 35 US‐P&F, 11 US‐NB, and 13 BN biopsies), 41 of the 159 procedures performed on small joints at baseline (11 US‐P&F, 20 US‐NB, and 10 BN biopsies), and 34 sequential biopsy procedures were evaluated. Compared to all other techniques evaluated in the small and large joints, fewer small joint BN biopsies and a significantly lower proportion of large joint BN biopsies yielded graded synovial tissue. No significant difference in either the proportion of graded tissue samples or total graded synovial tissue area between the US‐NB and arthroscopic large joint procedures was demonstrated. Among the sequential biopsy procedures evaluated (small joint US‐NB, large joint arthroscopy, US‐P&F biopsy, and BN biopsy), no significant difference in the proportion of graded synovial tissue or total graded synovial tissue area was demonstrated. All procedures yielded RNA of significant quality and quantity for subsequent transcriptomic analysis. Conclusion: These data support the integration of US‐guided methods along with arthroscopic biopsy for clinical trial protocols in which sequential sampling of synovium from the large and small joints is needed for both histologic and molecular analysis. BN biopsy may be considered if graded synovial tissue is not required for subsequent analyses.